Allergic reactions to foods in preschool-aged children in a prospective observational food allergy study - Fleischer, David M; Perry, Tamara T; Atkins, Dan; Wood, Robert A; Burks, A Wesley; Jones, Stacie M; Henning, Alice K; Stablein, Donald; Sampson, Hugh A; Sicherer, Scott H (Pediatrics (Evanston), 2012)
To examine circumstances of allergic reactions to foods in a cohort of preschool-aged children. We conducted a prospective, 5-site observational study of 512 infants aged 3 to 15 months with documented or likely allergy to milk or egg, and collected data prospectively examining allergic reactions. Over a median follow-up of 36 months (range: 0-48.4), the annualized reaction rate was 0.81 per year (367/512 subjects reporting 1171 reactions [95% confidence interval: 0.76-0.85]). Overall, 269/512 (52.5%) reported >1 reaction. The majority of reactions (71.2%) were triggered by milk (495 [42.3%]), egg (246 [21.0%]), and peanut (93 [7.9%]), with accidental exposures attributed to unintentional ingestion, label-reading errors, and cross-contact. Foods were provided by persons other than parents in 50.6% of reactions. Of 834 reactions to milk, egg, or peanut, 93 (11.2%) were attributed to purposeful exposures to these avoided foods. A higher number of food allergies (P < .0001) and higher food-specific immunoglobulin E (P < .0001) were associated with reactions. Of the 11.4% of reactions (n = 134) that were severe, 29.9% were treated with epinephrine. Factors resulting in undertreatment included lack of recognition of severity, epinephrine being unavailable, and fears about epinephrine administration. There was a high frequency of reactions caused by accidental and nonaccidental exposures. Undertreatment of severe reactions with epinephrine was a substantial problem. Areas for improved education include the need for constant vigilance, accurate label reading, avoidance of nonaccidental exposure, prevention of cross-contamination, appropriate epinephrine administration, and education of all caretakers.